Revealing how internal sensors in a smart battery impact the local graphite lithiation mechanism - Annabel Olgo; Sylvie Genies; Romain Franchi; Cédric Septet; Quentin Jacquet; Quentin Berrod; Rasmus Palm; Pascale Chenevier; Elise Villemin; Claire Villevieille; Nils Blanc; Samuel Tardif; et al. (Nature Communications, 2024)
Abstract Smart batteries, i.e., equipped with internal and external sensors, are emerging as promising solutions to enhance battery state of health and optimize operating conditions. However, for accurate correlations between the evolution of the cell parameters (e.g., temperature, strain) and physicochemical degradation mechanisms, it is crucial to know the reliability of sensors. To address this question, we perform a synchrotron operando X-ray diffraction experiment to investigate the local and global impact of the presence of internal sensors on a commercial prismatic Li-ion battery cell at various (dis)charge rates. We find that, while the overall electrochemical performance is unaffected, the sensors have a substantial impact on the local graphite lithiation kinetics, especially at high (dis)charge rates. These results show the importance of controlling local deformations induced by internal sensors and tailoring the dimensions of these sensors to obtain reliable battery performance indicators and optimize smart batteries.